ANALISIS KOMPARASI PENDAPATAN USAHATANI PETANI KONVERSI KARET KE KELAPA SAWIT DI KECAMATAN BAJUBANG KABUPATEN BATANGHARI - Saputra, Ardhiyan; Nurchaini, Dewi Sri (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2020)
Plantation is a source of foreign exchange and a source of employment. Commodities included in the plantation sub-sector are oil palm, rubber, coconut, coffee, tea and so on. The plantation sub-sector commodities that play an important role as a source of foreign exchange are oil palm and rubber. This study aims to determine the comparison of income from rubber farming whose land is converted to oil palm in Bajubang District, Batanghari Regency. This research was conducted in two villages in Bajubang subdistrict, namely Penerokan Village and Ladang Peris Village. The number of samples was 50 farmers, consisting of 25 rubber farmers who did not convert rubber plantation land to oil palm and 25 rubber farmers who had converted their rubber plantation land to oil palm. Sampling was done by using purposive sampling method. Based on the results of the independent sample t test, the sig (2-tailed) value of 0.000 is smaller than the value of Î± = 5%, which means there is a difference in the farm income of farmers who convert rubber land to oil palm. The amount of farm income that does not convert rubber land to oil palm is IDR 8,518,298 // Ha / year, while the income of farmers who convert rubber land to oil palm is IDR. 14,412,748 / Ha / Year.